2023
DOI: 10.1038/s41467-023-36365-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying glycan consumers in human gut microbiota samples using metabolic labeling coupled with fluorescence-activated cell sorting

Abstract: The composition and metabolism of the human gut microbiota are strongly influenced by dietary complex glycans, which cause downstream effects on the physiology and health of hosts. Despite recent advances in our understanding of glycan metabolism by human gut bacteria, we still need methods to link glycans to their consuming bacteria. Here, we use a functional assay to identify and isolate gut bacteria from healthy human volunteers that take up different glycans. The method combines metabolic labeling using fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…To determine if metabolic labeling of gut bacteria was possible using a large maltodextrin oligomer, we first applied our previously published pipeline with MAL-F using human stool samples . Fecal samples were collected from 10 healthy unrelated human volunteers under our approved protocol (A04-M27-15B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine if metabolic labeling of gut bacteria was possible using a large maltodextrin oligomer, we first applied our previously published pipeline with MAL-F using human stool samples . Fecal samples were collected from 10 healthy unrelated human volunteers under our approved protocol (A04-M27-15B).…”
Section: Resultsmentioning
confidence: 99%
“…However, we have also observed that bacteria labeled by a fluorescent glycan do not automatically use the glycan for growth, and therefore, validation is required for the low abundant O. formigenes. 51,59 For its part, E. eligens has been reported as unable to grow on amylose or amylopectin, yet the strain ATCC 27750 encodes 6 GH13s. 60 One of these GH13 genes is found neighboring a major facilitator superfamily (MFS) transporter gene, which suggests potential for oligosaccharide uptake.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intestinal microbiota is vital to the human body as it assists in digestion, releases essential nutrients, normalizes metabolism, participates in the immune system, and protects against various diseases. 80 Advances in genetic and analytical tools and methods have revealed that the gut microbiota are complex and diverse and may be associated with certain diseases. For example, the composition of the gut microbiota affects mucosal integrity, GI tract development, pathogen invasion, and nutrient absorption and assimilation.…”
Section: Gut Microbiota and Necrotizing Enterocolitismentioning
confidence: 99%